2018
DOI: 10.15171/ijhpm.2018.18
|View full text |Cite
|
Sign up to set email alerts
|

How and Where Do We Ask Sensitive Questions: Self-reporting of STI-associated Symptoms Among the Iranian General Population

Abstract: Background: Reliable population-based data on sexually transmitted infections (STI) are limited in Iran and self-reporting remains the main source of indirect estimation of STI-associated symptoms in the country. However, where and how the questions are asked could influence the rate of self-reporting. In the present study, we aimed to assess what questionnaire delivery method (ie, face-to-face interview [FTFI], self-administered questionnaire [SAQ], or audio self-administered questionnaire [Audio-SAQ]) and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…33 Moreover, these programs would not often cover the sexual health needs of those who might have extra marital sex, perhaps due to cultural taboos and religious values in the country. 29,34…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Moreover, these programs would not often cover the sexual health needs of those who might have extra marital sex, perhaps due to cultural taboos and religious values in the country. 29,34…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies in Iran have shown that cultural and religious restrictions might limit reporting sensitive information such as sexual practices or intercourses, and that people are more likely to disclose this information in the street-based surveys in comparison with telephone or home-based surveys. 28,29 As a result, participants were recruited from public places and crowded streets in urban areas. In fact, urban areas were divided in five regions (north, east, west, south and central) and two public places were selected from each region.…”
Section: Methodsmentioning
confidence: 99%
“…We implemented a street-based convenience sample in part because web-based services covering the general population are not available. Street-based sampling has been found to very feasible in comparison to random sampling via households, especially when investigating sensitive topics (61). Based on previous studies, we stratified Kerman based on the socio-economic status (low, medium, and high) (62,63).…”
Section: Participants and Study Designmentioning
confidence: 99%
“…While we employed a convenience street-based sampling strategy (which still yielded a high response rate) due to its feasibility in the study context (61), future research should aim for national samples to counteract potential sampling biases.…”
Section: Strengths Limitations and Directions For Future Researchmentioning
confidence: 99%
“…However, our previous experiences suggested that street-based sampling was the optimum approach in the case of sensitive characteristics in Iran. 55,56…”
Section: Limitationsmentioning
confidence: 99%